Efficiency-wage unemployment and endogenous growth - Jürgen Meckl (Universität Konstanz, Fakultät für Wirtschaftswissenschaften und Statistik, 1999)
This paper examines positive and normative implications of efficiency-wage induced unemployment within a model of endogenous growth. Sectorspecific impacts of the wage rate on labor efficiency establish a correlation between the growth rate and the rate of unemployment. The sign of this correlation is shown to be given by the intersectoral wage differential. Despite the existence of unemployment, decisive positive properties of the full-employment model are preserved. However, welfare implications of the full-employment model may be reversed. The optimal policy can be to reduce growth, while at the same time raising unemployment.
Keywords: E24; O40; 330; innovation-based growth; unemployment; efficiency wages